Antidiabetic effects of Brucea javanica seeds in type 2 diabetic rats. Issue 1 (December 2017) - Ablat, Abdulwali; Halabi, Mohammed; Mohamad, Jamaludin; Hasnan, Muhammad; Hazni, Hazrina; Teh, Ser-huy; Shilpi, Jamil; Mohamed, Zulqarnain; Awang, Khalijah
Abstract Background Brucea javanica (B. javanica ) seeds, also known as "Melada pahit " in Indo-Malay region are traditionally used to treat diabetes. The objective of this study was to determine antidiabetic, antioxidant and anti-inflammatory effects ofB. javanica seeds on nicotinamide (NA)-streptozotocin (STZ) induced type 2 diabetic (T2D) rats and to analyze its chemical composition that correlate with their pharmacological activities. Methods A hydroethanolic extract ofB. javanica seeds was fractionated with n-hexane, chloroform and ethyl acetate. An active fraction was selected after screening for its ability to inhibit α-glucosidase and glycogen phosphorylase α (GP-α). Isolation and characterization were carried out by using column chromatography, NMR and LCMS/MS. All isolates were assayed for inhibition of GP-α and α-glucosidase. Antidiabetic effect of active fraction was further evaluated in T2D rat model. Blood glucose and body weight were measured weekly. Serum insulin, lipid profile, renal function, liver glycogen and biomarkers of oxidative stress and inflammation were analyzed after 4-week treatment and compared with standard drug glibenclamide. Results Ethyl acetate fraction (EAF) exerted good inhibitory potential for α-glucosidase and GP-α compared with other fractions. Chromatographic isolation of the EAF led to the identification of seven compounds: vanillic acid (1), bruceine D (2), bruceine E (3), parahydroxybenzoic acid (4), luteolin (5), protocatechuic acid (6), and gallic acid (7). Among them, Compound (5) was identified as the most potent inhibitor of GP-α and α-glucosidase and its GP-α inhibitory activity (IC50  = 45.08 μM) was 10-fold higher than that of caffeine (IC50  = 457.34 μM), and α-glucosidase inhibitory activity (IC50  = 26.41 μM) was 5.5-fold higher than that of acarbose (IC50  = 145.83 μM), respectively. Compounds (4), (6), and (7) inhibited GP-α activity in a concentration-dependent manner with IC50 values of 357.88, 297.37, and 214.38 μM, and their inhibitory effect was higher than that of caffeine. These compounds exhibited weak potency on α-glucosidase compared with acarbose. Compounds (1), (2), and (3) showed no inhibition on both GP-α and α-glucosidase. In vivo study showed that EAF treatment significantly reduced blood glucose level, increased insulin and glycogen contents, decreased markers of oxidative stress and inflammation, and lipid levels in T2D rats compared with untreated group. Conclusions The EAF has potential therapeutic value for the treatment of T2D via acting as GP-α and α-glucosidase inhibitors by improving hepatic glucose and carbohydrate metabolism, suppressing oxidative stress, and preventing inflammation in T2D rats. According to the results, the efficacy of EAF could be due to the presence of luteolin along with synergistic effect of multiple compounds such as parahydroxybenzoic acid, protocatechuic acid, and gallic acid inB. javanica seeds.